2013
DOI: 10.22502/jlmc.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Aerodigestive and Ear Foreign Bodies at Lumbini Medical College

Abstract: Introduction: Aerodigestive and Ear foreign bodies are common Ear Nose Throat (ENT) emergencies. They arecommonly encountered by otolaryngologists, paediatricians, and primary care physicians. Objective: The aim ofthis study is to analyze different types of foreign bodies and sociodemographic correlates of self-inflicted foreign body insertion in ear, nose and throat.   Method: Seventy-four patients with aerodigestive foreign body coming to our Hospital over a period of one year, starting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our study showed male predominance with Male: Female ratio of 1.55:1 which is also supported by other studies. 2 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed male predominance with Male: Female ratio of 1.55:1 which is also supported by other studies. 2 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Foreign body is common in children because they are naturally curious about their surroundings and about body orifices hence inclined to place foreign bodies in ear, nose or oral cavity. 2 …”
Section: Introductionmentioning
confidence: 99%